Madrasah Tsanawiyah Principal Competency-Based Supervision Management Model (Fakultas Ekonomi, Universitas Negeri Semarang, 2017)
This research aims to develop a competency-based supervision model as a strategy to address the quality of education issues in Madrasah Tsanawiyah. The specific objective of this research is to identify various aspects that need to be prepared in supervision development, designing and piloting the model and analyzing the effectiveness of the competency-based supervision model by the principal of madrasah in teacher’s professionalism improvement. The research method used Research and Development (RD) with the following stages: research and information gathering, planning, product development, testing, and final product improvement stage. The supervision activities consist of three activities, namely planning, implementation and supervision follow-up. The supervision planning activity is technical guidance planning. The planning is centered on the principal as a supervisor and teacher involvement as the supervision object. The supervision implementation is held twice every semester towards teacher and learning by using directive model. The supervision follow-up activities are learning improvements. The overall supervision implementation has gone well with the score of 83.3. Most of the Madrasahs have conducted scheduled and periodic supervision. The development of supervision modell that emphasizes the Madrasah Tsanawiyah principal’s competence strengthening is done by developing the focus and objectives of the supervision, not only in the academic aspect, but also the managerial aspect and the human resources improvement through the implementation of collaborative management.